Analysis of Accounting Information Systems on Production and Sales Effectiveness at PT. Gresik Cipta Sejahtera Labuhan Batu Branch, Indonesia - Ritonga, Tri Agustin; Nurwani, N.; Syafina, Laylan (Manunggal Halim Jaya, 2025)
This study aims to determine whether the accounting information system for production and sales at PT Gresik Cipta Sejahtera Labuhan Batu Branch has been running effectively or not. The focus of this branch is to ensure the smooth running of the production and sales process. The use of an efficient accounting information system can increase production effectiveness by ensuring that fertilizer stock is always available on time and in the right amount. In addition, this system can also support sales strategies by providing relevant information for decision making related to price, promotion, and distribution. This study uses a descriptive qualitative approach to understand the impact of accounting information systems on operational effectiveness. Primary data were obtained through interviews and direct observation. The results of the study indicate that the raw material inventory accounting information system implemented at PT Gresik Cipta Sejahtera is quite reliable in recording and reporting inventory data. Although the existing system is quite effective, the study also identified several parts that need improvement, such as the need for further consistency between the inventory module and the sales module to increase the accuracy of estimating fertilizer stock needs based on sales trends.